Modelling the Athabasca watershed snow response to a changing climate - Dibike, Yonas; Eum, Hyung-Il; Prowse, Terry (Journal of Hydrology: Regional Studies, 2018)
Study region: The Athabasca River basin (ARB) with its head-waters located within the Canadian Rockies. Study focus: Investigating the snow response of the Athabasca watershed to projected climate using the Variable Infiltration Capacity (VIC) hydrologic model and statistically downscaled future climate data from a selected set of CMIP5 GCMs forced with RCP4.5 and RCP8.5 emissions scenarios. New hydrological insights for the region: High resolution end-of-century projections of SWE over the Athabasca watershed show an overall decreasing trend in the mean monthly SWE over the watershed, with the largest decreases occurring in March and April, especially in the high-elevation sub-basin. There are also widespread decreases in annual maximum SWE (SWEmax), with the middle-basin showing slight increases under the RCP4.5 scenario. The dates of SWEmax are generally getting earlier, with RCP4.5 showing a less linear response than RCP8.5. Increases in early spring snowmelt are followed by decreases during the late spring and summer months mainly as a result of earlier start of snowmelt. An overall decrease in snow-cover duration of up to fifty days is projected with the largest decrease occurring in the high elevation sub-basin. Such projected declines in snow water storage and a shift to earlier peak SWE and snowmelt over the ARB have significant implications for the magnitude and timing of the watershed soil-moisture content and hydrologic regime of the Athabasca River. This study was conducted with the financial support provided by the Environment and Climate Change Canada’s Climate Change Adaptation program and the Joint Alberta and Environment and Climate Change Canada Oil-sands Monitoring Program (JOSMP). The authors would like to thank the University of Washington Computational Hydrology group for making the VIC hydrologic model available and the Pacific Climate Impacts Consortium (PCIC), at the University of Victoria, for providing the downscaled daily Canada-wide high-resolution climate-change scenario data. ...